Implementasi Fast Fourier Transform dalam Pengembangan Alat dan Bantuan Program Untuk Mengukur Total Harmonic Distortion - setya - ardhi; Judi Prajetno Sugiono; Hari Sutikno; Ivan B. Sasaka (LPPM STIKI MALANG, 2019)
Total Harmonic Distortion (THD) is one parameter that states the quality of an electrical signal that is to be used compared to pure sinusoidal signals. THD is a measure that states how much the signal is no longer shaped like the original. With Fourier Analysis, the THD magnitude is expressed as a comparison of the geometric mean of the root number of the harmonic square of the frequency fundamental.This study aims to build a THD measuring device using the AVR microcontroller to digitally calculate THD. Calculation of signal harmonics in Fourier series is not done in the traditional way, but is done using the Fast Fourier Transform (FFT) algorithm. This algorithm in numerical computation will provide a better calculated speed compared to traditional calculations. The measuring device is test using several forms of signals, then the results will be compared with results calculated on a computer. The results of the trial show that this method can provide accuracy in measuring the THD size of a signal properly.